2017
DOI: 10.4103/cytojournal.cytojournal_12_17
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver reproducibility of The Paris System for Reporting Urinary Cytology

Abstract: Background:The Paris System for Reporting Urinary Cytology represents a significant improvement in classification of urinary specimens. The system acknowledges the difficulty in cytologically diagnosing low-grade urothelial carcinomas and has developed categories to deal with this issue. The system uses six categories: unsatisfactory, negative for high-grade urothelial carcinoma (NHGUC), atypical urothelial cells, suspicious for high-grade urothelial carcinoma, high-grade urothelial carcinoma, other malignanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(83 citation statements)
references
References 23 publications
(44 reference statements)
5
78
0
Order By: Relevance
“…In a study reporting inter‐observer reproducibility for the Paris system of reporting urinary cytology, the authors found an average absolute agreement of 65% with an average expected agreement of 44%. The calculated Kappa was 0.32 . Importantly, approximately 15% of disagreements were classified as having a high clinical impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study reporting inter‐observer reproducibility for the Paris system of reporting urinary cytology, the authors found an average absolute agreement of 65% with an average expected agreement of 44%. The calculated Kappa was 0.32 . Importantly, approximately 15% of disagreements were classified as having a high clinical impact.…”
Section: Discussionmentioning
confidence: 99%
“…For a diagnostic categorization system to be clinically useful it must show good inter‐observer reproducibility. Previously published diagnostic categorization schemes for urinary cytology and respiratory cytology have had variable degrees of inter‐observer reproducibility . We are unaware of a prior study investigating the inter‐observer diagnostic reproducibility of the Milan System for Salivary Gland Cytopathology.…”
Section: Introductionmentioning
confidence: 94%
“…Third, because the questionnaire was mailed in July 2014, the data of TPS utilization may not reflect the current situation, at least in certain aspects, because TPS was published in 2016, and since then many institutions have likely implemented it. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Finally, although information about TPS has been widely disseminated, in particular in the cytopathology community, there is still a need for education about TPS, most importantly for our clinical colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that using the set of standardized criteria in TPS has generally resulted in a reduction of the interinstitutional variation of “atypical urothelial cells” (AUC) rates compared with their pre‐Paris rates, from 6.60% to 41.20% (a 34.6% range) to 5.30% to 26.00% (a 20.7% range) 12‐18 . Most institutions experienced decreases in AUC rates; the sole outlier in a recent review of the literature was an institution with very low pre‐Paris AUC rates and the reason for an increase in AUC in this single institution was an overinterpretation of the morphologic criteria for atypia 19 .…”
Section: Strengthsmentioning
confidence: 99%